A biomimetic metal–organic framework with cuboid inner cavities for enantioselective separation. Issue 11 (28th April 2022) - Zhu, Chengfeng; Zhang, A-Mei; Li, Ying; Li, Han-Xue; Qian, Yijian; Fu, Yanming; Wu, Xiang; Li, Yougui
Abstract : A biomimetic metal–organic framework with cuboid inner cavities and multiple recognition sites was constructed from a phenylalanine-derived ligand. It can enantioselectively separate various racemic alcohols, diols and epoxides with ee up to 99.5%. Abstract : A chiral metal–organic framework (CMOF) with accessible binding pockets and multiple recognition sites is constructed from a tricarboxylate ligand derived from phenylalanine. The CMOF features a rare structure with cavities encapsulated by a non-coordinated amino-acid moiety. It has been proven to be an efficient and recyclable chiral host, enabling adsorbing and separating racemic alcohols, diols, and epoxides with excellent enantioselectivity.